Peningkatan Ketrampilan dan Pengetahuan Bahasa Jerman bagi Siswa SMA Negeri 8 Ambon - Juliaans E. R. Marantika; Jolanda Tomasouw; Chindy Claudia Ririhena; Ronald Darlly Hukubun (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
Foreign language proficiency plays a crucial role in the era of globalization, where intercultural communication skills are increasingly essential. German, as one of the major international languages widely used in education, technology, and industry, offers significant opportunities for Indonesian students to compete globally. However, the teaching and learning of German at SMA Negeri 8 Ambon still face several challenges, including limited learning resources, insufficient practice time, and low student motivation. This community service program aims to enhance students’ German language skills through education focusing on the four key competencies: Schreiben (writing), Sprechen (speaking), Hören (listening), and Lesen (reading), using a participatory action model. This approach actively involves students in the learning process through stages of problem identification, action planning, implementation, and reflection. The results indicate a significant improvement in students’ understanding and proficiency across the four language skills. Furthermore, students demonstrated high levels of enthusiasm and engagement throughout the program, reflecting the effectiveness of the participatory approach in fostering motivation and interest in foreign language learning. Therefore, this program contributes positively to strengthening German language competence among students at SMA Negeri 8 Ambon, equipping them with essential skills to face future global challenges.